2013
DOI: 10.1039/c3cc41333k
|View full text |Cite
|
Sign up to set email alerts
|

A new route to prepare multiresponsive organogels from a block ionomer via charge-driven assembly

Abstract: We report a novel route to prepare multiresponsive organogels through charge-driven assembly between a block ionomer and a diblock copolymer. The ionic complex aggregates to form spherical cores, which are connected by the middle block of the block ionomer to form gels. The organogels are responsive to acids, amines and salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(17 reference statements)
1
17
0
Order By: Relevance
“…12 Fang and co-workers reported preparation of HIPE organogels from bulk organogels based on low molecular weight gelators and found that the mechanical strength of the HIPE organogels was dominated by the continuous phase. 6,14 Herein we demonstrate for the first time that HIPE organogels can be prepared from polymer organogels which are usually inexpensive in comparison with organogels prepared from low molecular weight organogelators. 13 In our previous study, we developed a new route to prepare multiresponsive organogels by charge-induced assembly of a triblock ionomer, sulfonated polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (SSEBS), and a diblock copolymer polystyrene-block-poly(2-vinyl pyridine) (PS-b-P2VP).…”
Section: Tao Zhang and Qipeng Guo*mentioning
confidence: 92%
See 1 more Smart Citation
“…12 Fang and co-workers reported preparation of HIPE organogels from bulk organogels based on low molecular weight gelators and found that the mechanical strength of the HIPE organogels was dominated by the continuous phase. 6,14 Herein we demonstrate for the first time that HIPE organogels can be prepared from polymer organogels which are usually inexpensive in comparison with organogels prepared from low molecular weight organogelators. 13 In our previous study, we developed a new route to prepare multiresponsive organogels by charge-induced assembly of a triblock ionomer, sulfonated polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (SSEBS), and a diblock copolymer polystyrene-block-poly(2-vinyl pyridine) (PS-b-P2VP).…”
Section: Tao Zhang and Qipeng Guo*mentioning
confidence: 92%
“…13 In our previous study, we developed a new route to prepare multiresponsive organogels by charge-induced assembly of a triblock ionomer, sulfonated polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene (SSEBS), and a diblock copolymer polystyrene-block-poly(2-vinyl pyridine) (PS-b-P2VP). 14 By tuning the hydrophilicity of amines used, ionic complexes can stabilize water droplets in organic solvents, leading to the macrophase separation in the gels. When the volume fraction of water droplets in gels exceeds 74%, HIPE gels form.…”
Section: Tao Zhang and Qipeng Guo*mentioning
confidence: 99%
“…They synthesized ionic complex aggregates originating from two organic‐solvent‐soluble components: a block ionomer consisting of two acidic sulfonated polystyrene blocks and a neutral solvophilic poly(ethylene‐ ran ‐butylene) block and a diblock copolymer polystyrene‐ block ‐poly(2‐vinylpyridine). The gelators could be formed rapidly in 20–30 seconds and the properties of the organogels could be finely tuned by acetic acid, triethylamine, and their salts 298. In another work, Jiang et al reported the synthesis of the cholesterol‐based salicylidene Schiff base derivative cholesterol 2‐(3,5‐di‐ tert ‐butyl‐2‐hydroxybenzylideneamino)acetate (CDBHA) which could self‐assemble into organogels with multi‐stimuli‐responsive properties.…”
Section: Multi‐stimuli‐responsive Bulk Gelsmentioning
confidence: 99%
“…19 In brief, 20 g of polystyrene was dissolved in 200 mL of dichloroethane, and the required amount of freshly prepared acetyl sulfonate was added at 50 1C. 19 In brief, 20 g of polystyrene was dissolved in 200 mL of dichloroethane, and the required amount of freshly prepared acetyl sulfonate was added at 50 1C.…”
Section: Preparation Of Spssmentioning
confidence: 99%
“…12 However, a large number of microgel particles (5 wt% of oil phase) are required to obtain HIPEs. 14,18,19 In this paper, we report that water-in-oil HIPEs have been obtained by the phase inversion of oil-in-water emulsions with an ionomer as the stabilizer, where only 0.2 (w/v)% of the continuous phase is required to stabilize the HIPEs. 15,16 Until now, the preparation of HIPEs by phase inversion is still rare, and the phase inversion of oil-in-water emulsions to form water-in-oil HIPEs with low stabilizer concentrations is highly desirable, since most monomers used for poly(HIPEs) are oleophilic.…”
Section: Introductionmentioning
confidence: 99%